Fabrication and characteristics of multifunctional hydrogel dressings using dopamine modified hyaluronic acid and phenylboronic acid modified chitosan - Han, Yanting; Cao, Jing; Li, Man; Ding, Peng; Yang, Yujie; Okoro, Oseweuba Valentine; Sun, Yanfang; Jiang, Guohua; Shavandi, Amin; Nie, Lei (Frontiers in Chemistry, 2024)
The healing of damaged skin is a complex and dynamic process, and the multi-functional hydrogel dressings could promote skin tissue healing. This study, therefore, explored the development of a composite multifunctional hydrogel (HDCP) by incorporating the dopamine modified hyaluronic acid (HA-DA) and phenylboronic acid modified chitosan (CS-PBA) crosslinked using boric acid ester bonds. The integration of HA-DA and CS-PBA could be confirmed using the Fourier transform infrared spectrometer and 1 H nuclear magnetic resonance analyses. The fabricated HDCP hydrogels exhibited porous structure, elastic solid behavior, shear-thinning, and adhesion properties. Furthermore, the HDCP hydrogels exhibited antibacterial efficacy against Gram-negative Escherichia coli (E. coli) and Gram-positive Staphylococcus aureus (S. aureus). Subsequently, the cytocompatibility of the HDCP hydrogels was verified through CCK-8 assay and fluorescent image analysis following co-cultivation with NIH-3T3 cells. This research presents an innovative multifunctional hydrogel that holds promise as a wound dressing for various applications within the realm of wound healing.